Penerapan Model PBL pada Materi Teks Persuasif dan Analisis Persepsi Siswa terhadap Model Tersebut (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study aims to describe the application of the Problem-Based Learning (PBL) model to persuasive text material and analyze students' perceptions of the model. The approach used is descriptive qualitative, with 61 students of class VIII of SMP Muhammadiyah 3 Banjarmasin as research subjects. Data were obtained through RPP documentation, poster invitation assignment results, and closed questionnaires that measured students' perceptions. The results of the study indicate that the application of the PBL model has followed the syntax of problem-based learning systematically and has succeeded in improving students' understanding and skills in composing persuasive texts. All students scored above the KKM, with scores ranging from 80 to 95. In addition, the results of the questionnaire revealed that the majority of students responded positively to this model. They felt that learning was more interesting, contextual, and helped them think critically and independently. Thus, the PBL model has proven to be effective and feasible to be applied in Indonesian language learning to increase student involvement and competence.